Efektivitas Program Kegiatan Layanan Anak di Perpustakaan Daerah Kabupaten Deli Serdang - Salsabila Naqiyyah Melfan; Abdul Karim Batubara (Mudir : Jurnal Manajemen Pendidikan, 2023)
The Development and Operationof the library depends on the pattern of Peoples’s lives,the information needed,of the community, and the ability of the community to understand the use odf technology. The public library which is an educational institution aimed at the community as a provider or various information, according to the scientific needs of all levels of society. Give this, it means that libraries have a very big hole in increasing interest in reading. The existance of a children’s service program, which is aimed at children, makes children experience faster growth and development of the ability to think and have broad insights. The research method used is qualitative research, namely collecting primary data through the results of observations, interviews and documentation. And Secondary data in the form of Literature Review sourced from Journals, Books and the Internet. The results showed that the Children's Services at the Regional Library of Deli Serdang Regency were effective, this was seen from the large number of visitors who packed the children's room every day, and adequate facilities. However, it is necessary to develop human resources in this library.